Who was Clara Barton? - Spinner, Stephanie; Groff, David 1956- (New York, New York, USA Grosset & Dunlap, an imprint of Penguin Group (USA) LLC, 2014)
Profiles the life and accomplishments of Clara Barton, a teacher who organized efforts to bring nursing care to wounded soldiers during the Civil War and who went on to become the founder of the American Red Cross.
Includes bibliographical references (pages 104-106).
Keywords: Barton, Clara -- 1821-1912 -- Juvenile literature; Barton, Clara -- 1821-1912.; American Red Cross -- Biography -- Juvenile literature; American Red Cross; Nurses -- United States -- Biography -- Juvenile literature; Nurses; Women -- Biography; United States; Biography